2018
DOI: 10.1111/jvs.12631
|View full text |Cite
|
Sign up to set email alerts
|

Projected regional forest plant community dynamics evidence centuries‐long effects of habitat turnover

Abstract: Questions Many Western European and North American countries have been experiencing strong reforestation in the last two centuries due to agricultural abandonment. Other land‐use changes, such as urbanization, can simultaneously trigger forest erosion. In this context of habitat turnover, forest understorey plant dynamics depend on the balance between immigration credit in post‐agricultural forest and extinction debt in ancient forest. The transient and final community properties following concomitant habitat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…Further, a recent modelling approach indicated that AFS have a low turn-over rate in which Petersen (1994), Graae (2000), Graae, Sunde, and Fritzboger (2003) France Dupouey, Sciama, Dambrine, and Rameau (2002), Sciama et al (2009), Bergès et al (2016), Germany Wulf (1997), Schmidt et al (2014) Great Britain Rackham (1980) Hermy et al (1999), Verheyen et al (2003), Hermy and Verheyen (2007) TA B L E 1 Lists of ancient forest species by country or region. Updated information based on Hermy (2015) limited colonization capacity is associated with a low propensity for extinction (Lalechère, Jabot, Archaux, & Deffuant, 2017); this increases their colonization potential (Lalechère et al, 2018).…”
Section: Ancient Forest Plants: a Guild Of Forest Specialistsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, a recent modelling approach indicated that AFS have a low turn-over rate in which Petersen (1994), Graae (2000), Graae, Sunde, and Fritzboger (2003) France Dupouey, Sciama, Dambrine, and Rameau (2002), Sciama et al (2009), Bergès et al (2016), Germany Wulf (1997), Schmidt et al (2014) Great Britain Rackham (1980) Hermy et al (1999), Verheyen et al (2003), Hermy and Verheyen (2007) TA B L E 1 Lists of ancient forest species by country or region. Updated information based on Hermy (2015) limited colonization capacity is associated with a low propensity for extinction (Lalechère, Jabot, Archaux, & Deffuant, 2017); this increases their colonization potential (Lalechère et al, 2018).…”
Section: Ancient Forest Plants: a Guild Of Forest Specialistsmentioning
confidence: 99%
“…colonisation credit Lalechère et al (2018). propose a metapopulation dynamics modelling approach to assess relaxation time following simultaneous ancient forest loss and afforestation on former agricultural lands; they applied this approach to AFS and non-AFS in a large landscape in northern France.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some observations related a positive correlation between the payment of the extinction debt and patch area but also a negative correlation between these payment and fragmentation degree (Ferraz et al, ; Halley, Iwasa, & Vokou, ). More precisely, Lalechère, Jabot, Archaux, and Deffuant () showed that the relaxation time depends on functional connectivity and that dispersal distance mediates the strength of this relationship. Their results were based on the analyses of contrasted forest plant species (according to dispersal and turnover rates) inventoried in a French region.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the equivalent connectivity index compared two static independent landscape graphs (in 2020 and 2050) to provide information about the actual and future need for conservation actions, but did not evaluate metapopulation dynamics over time. We point out that the equivalent connectivity index can be incorporated into discrete time metapopulation models to evaluate species dynamics and the speed of colonization and extinction processes over time (Lalechère et al, 2018).…”
Section: Study Limitationsmentioning
confidence: 99%